'SURFACE IS AN ILLUSION BUT SO IS DEPTH': THE NOVELS OF CHRISTIAN KRACHT. (19th March 2013) - Finlay, Frank
ABSTRACT This detailed discussion of the entirety of Kracht's fictional œuvre is an effort to re‐position and reassess him both in the critical literature and in relation to longer‐term literary trends. With reference to Faserland, I identify the key fault lines in the often conflicting scholarly and critical reception of Kracht's work, most notably the consensus which has emerged that beneath his apparent preoccupation with 'surface' there is significant seriousness or 'depth' intended. I then discuss the novels 1979, Ich werde hier sein im Sonnenschein und Schatten and Imperium to identify their underlying thematic and aesthetic continuities in order to interrogate this mainstream view. In particular, I contend that for all their apparent engagement with historical, philosophical and socio‐cultural issues, such as national identity and the search for 'Heimat', highly ludic elements, including a heightened intertextuality and intermediality, run through all the texts. These serve Kracht's self‐conscious intent to alienate and entertain the reader in order to playfully insist on his novels' status as artefacts, thereby deliberately debunking their seriousness. Kracht's dominant mode is humour, his style pastiche: a mark of individual distinction in an otherwise crowded literary landscape with its frequently 'realistic' focus on historical and contemporary concerns. Dieser Beitrag beschäftigt sich mit dem umstrittenen Schriftsteller Christian Kracht und gilt als Versuch, vor dem Hintergrund der Forschungsliteratur sowie aktueller Trends sein gesamtes Romanwerk in der gegenwärtigen literarischen Landschaft der Bundesrepublik zu verorten. Ausgehend von der Rezeption des Debütromans Faserland (1995) wird auf einen inzwischen breiten kritischen Konsens hingewiesen, nach dem Krachts Werke trotz ihrer Beschäftigung mit der 'Oberfläche' sich durchaus 'tiefsinningen' Themen widmen. Anhand einer Untersuchung von den Romanen 1979, Ich werde hier sein im Sonnenschein und Schatten und Imperium wird diese Position revidiert. Die ästhetischen und thematischen Konstanten im Werk werden hervorgehoben, um zu behaupten, dass den Romanen Krachts eine durchaus spielerische Dimension innewohnt, die den konstatierten ethischen Ernst mit Absicht – und mit Humor – unterminiert. Krachts Duktus ist Pastiche: sein besonderer Beitrag zur Vielfalt der neuen erzählerischen Literatur seit der Wende, deren Haupttendenz auf einer eher 'realistischen' Beschäftigung mit der deutschen Geschichte und Gegenwart liegt.